2016
DOI: 10.1902/jop.2016.150722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Systemic T Helper 17 Cell Response; Gingival Expressions of Interleukin‐17 and Retinoic Acid Receptor‐Related Orphan Receptor γt; and Alveolar Bone Loss in Experimental Periodontitis

Abstract: Curcumin seems to be a promising host modulatory agent in periodontal disease pathogenesis regarding IL-17/IL-23 axis, with a decreasing effect on ABL and gingival expressions of IL-17 and RORγt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 49 publications
0
37
0
1
Order By: Relevance
“…Diabetes mellitus and periodontitis are complex chronic diseases with an established higher risk for the development periodontitis and future tooth loss in the presence of DM . CURC is a natural compound with promising effects in modulating the osteo‐immune‐inflammatory and antioxidant host response both in periodontally diseased sites and in diabetes and related complications . For the first time, this investigation assessed the natural curcumin's impact on the progression of EP in rats induced to DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes mellitus and periodontitis are complex chronic diseases with an established higher risk for the development periodontitis and future tooth loss in the presence of DM . CURC is a natural compound with promising effects in modulating the osteo‐immune‐inflammatory and antioxidant host response both in periodontally diseased sites and in diabetes and related complications . For the first time, this investigation assessed the natural curcumin's impact on the progression of EP in rats induced to DM.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the morphometric evaluations of the current study revealed that DM induction promoted higher periodontal disease progression and that diabetic rats treated with daily CURC + INS, as well as those Non‐DM, presented lower linear bone loss values in periodontitis sites, suggesting that the combined use of CURC and INS, and not the substances used alone, may positively influence periodontal breakdown, even in the presence of DM. Although promising effects of natural CURC on periodontal tissues have already been revealed in earlier experimental and also clinical studies, only few information is available concerning the influence of a chemically modified CURC on periodontitis in the presence of a recognized at‐risk condition as diabetes mellitus and there are no data revealing the impact of a natural CURC in the progression of EP associated with DM. Of importance, although some evidence has suggested that certain chemically modified CURC shows improved solubility and bioavailability in comparison with natural CURC, advantages related to the natural form of CURC include the facility to obtain the substance and greater possibility of using this therapeutic agent for clinical application in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of curcumin in decreasing MMP-2 and MMP-9 expression levels was reported in cancer cells, such as squamous cell carcinoma and osteoclastoma (Cao et al , 2015, Lee et al , 2015). Additionally, in vivo studies in humans and animals demonstrated curcumin’s effectiveness in decreasing the severity of periodontal diseases (Elburki et al , 2014, Nagasri et al , 2015, Bakir et al , 2016, Elburki et al , 2016). Curcumin has been investigated in many clinical trials for treatment of several disorders, such as ulcerative colitis (Baliga et al , 2012), breast cancer (Nagaraju et al , 2012), pancreatic cancer (Veeraraghavan et al , 2011), and diabetes (Abdel Aziz et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bakır et al [29] reported that curcumin acts a host modulatory agent in periodontal disease pathogenesis regarding IL-17/IL-23 axis, with a decreasing effect on alveolar bone loss and gingival expressions of IL-17 and retinoic acid receptor-related orphan receptor γ t .…”
Section: Discussionmentioning
confidence: 99%